Angiotensin II antagonists in myocardial infarction - Grabowski, Marcin; Filipiak, Krzysztof J.; Opolski, Grzegorz (Przewodnik Lekarza/Guide for GPs, 2005)
Angiotensin II receptor antagonists act by a different mechanism than the angiotensin converting enzyme inhibitors, although both reduce the stimulation of angiotensin II receptors. Trials of these agents have been conducted to determine whether they have a comparable benefit in patients with myocardial infarction. This article summaries current knowledge and recommendation for use angiotensin II antagonists in myocardial infarction.